Low-grade intraductal carcinoma of salivary glands: A systematic review of this rare entity - Francesco Giovacchini; Caterina Bensi; Stefano Belli; Maria Elena Laurenti; Martina Mandarano; Daniele Paradiso; Michele Giansanti; Antonio Tullio (Elsevier, 2019)
Background: Low-grade intraductal carcinomas are rare, malign tumors of salivary glands most commonly affecting parotid gland. It is a slow-growing tumor considered with a favourable prognosis after surgical excision. Methods: To define the characteristics and management of low-grade intraductal carcinoma a systematic review was performed using the electronic databases Pubmed, Cochrane and Scopus. A new case report was also described. Results: Including this case the review of literature identified only 54 cases reported thus far. Demographics, clinical presentation, diagnostic tools, treatment, follow-up and recurrence rate, histological and immunohistochemical patterns of this kind of tumor were summarized. Conclusion: Low-grade intraductal carcinoma has already been well defined but is important to focus on the fact that in few cases component of high-grade infiltrations have been reported: this may modify surgical approach because a simple tumorectomy may not be enough.